Our non-Christian nation: how atheists, Satanists, pagans, and others are demanding their rightful place in public life - Wexler, Jay (Redwood Press, 2019)
Mummies, monuments, and monotheism : religious displays as government speech -- Pagans, pentacles, and pluralism : religious displays in the public forum -- Secularism, statehouses, and schoolboards : prayers and invocations before government bodies -- The Satanic Temple : taking it to a whole 'nother level -- Muslims, money, and middle schools : government funding of religion -- Atheists, the Antichrist, and after school clubs : religious activities in the public schools